The Relation between Learning Styles according to the Whole Brain Model and Emotional Intelligence: A Study of University Students - Marta Estrada; Diego Monferrer; Miguel-Ángel Moliner (Universidad de Navarra, 2019)
There has been considerable academic interest in learning styles in recent decades aimed at developing more efficient methodologies in the teaching-learning process. However, few studies have analysed the existing relationship between learning styles according to the whole brain model and emotional intelligence in university students, the proposal of the present research. Methodology: Dominant learning styles were measured with the Whole Brain Theory Diagnosis, a shortened adaptation of the Herrmann Brain Dominance Instrument. Emotional intelligence was measured using a simplified adaptation of the Spanish version of the Trait Meta-Mood Scale. Results: Learning styles based on mixed dominances positively influence the development of emotional intelligence. Learning styles associated with the right hemisphere were also found to have a greater impact on emotional intelligence. Conclusions: Students should be trained in a learning style that enables the use of mixed dominances, thereby contributing to the development of their emotional intelligence.